SELENIUM AND THYROID HEALTH: THE CASE OF HASHIMOTO’S THYROIDITIS - Dilorom Anvarovna Urunbayeva; Shaxnoza Bakhtiyorovna Khudaybergenova (Western European Studies, 2025)
Hashimoto’s thyroiditis (HT) is one of the most prevalent autoimmune thyroid disorders and the leading cause of hypothyroidism worldwide. In recent years, selenium has attracted significant attention due to its essential role in thyroid hormone metabolism and its potential immunomodulatory and antioxidant properties. Selenium-dependent enzymes, such as glutathione peroxidases and iodothyronine deiodinases, are crucial for thyroid hormone synthesis and protection of thyroid tissue from oxidative damage. Several clinical studies have demonstrated that selenium supplementation can reduce thyroid autoantibody levels, particularly thyroid peroxidase antibodies (TPOAb), and improve the overall well-being of patients with HT. However, the results remain inconsistent, with some trials showing no significant benefit. This paper reviews the physiological role of selenium in thyroid health, the potential mechanisms underlying its effects in HT, and current evidence from clinical studies, highlighting both the therapeutic potential and limitations of selenium supplementation in patients with autoimmune thyroiditis
Keywords: Selenium; Hashimoto’s thyroiditis; thyroid health